Mechanical property analysis and design parameter optimization of a novel nitinol nasal stent based on numerical simulation - Yu, Hui; Zheng, Lingling; Qiu, Jikuan; Wang, Jiayue; Xu, Yaoke; Fan, Baoshi; Li, Rui; Liu, Junxiu; Wang, Chao; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2022)
Background: A novel braided nasal stent is an effective alternative to nasal packing after septoplasty that can be used to manage the mucosal flap after septoplasty and expand the nasal cavity. This study aimed to investigate the influence of design parameters on the mechanical properties of the nasal stent for optimal performance. Methods: A braided nasal stent modeling method was proposed and 27 stent models with a range of different geometric parameters were built. The compression behavior and bending behavior of these stent models were numerically analyzed using a finite element method (FEM). The orthogonal test was used as an optimization method, and the optimized design variables of the stent with improved performance were obtained based on range analysis and weight grade method. Results: The reaction force and bending stiffness of the braided stent increased with the wire diameter, braiding density, and external stent diameter, while wire diameter resulted as the most important determining parameter. The external stent diameter had the greatest influence on the elongation deformation. The influence of design parameters on von-Mises stress distribution of bent stent models was visualized. The stent model with geometrical parameters of 25 mm external diameter, 30° braiding angle, and 0.13 mm wire diameter (A3B3C3) had a greater reaction force but a considerably smaller bending stiffness, which was the optimal combination of parameters. Conclusions: Firstly, among the three design parameters of braided stent models, wire diameter resulted as the most important parameter determining the reaction force and bending stiffness. Secondly, the external stent diameter significantly influenced the elongation deformation during the compression simulation. Finally, 25 mm external diameter, 30° braiding angle, and 0.13 mm wire diameter (A3B3C3) was the optimal combination of stent parameters according to the orthogonal test results.